Association of Environmental Sanitation and Personal Hygiene with Skin Health Complaints among Residents in Ibul Besar II - M.Ricko; Ema Hermawati; Yustini Ardillah; Elvi Sunarsih; Laura Dwi Pratiwi (Poltekkes Kemenkes Surabaya, 2026)
Skin health problems remain a common public concern, influenced by poor environmental sanitation and inadequate personal hygiene practices. Ibul Besar II Village is a suburban locale traversed by a tributary of the Ogan River. Data from the Pegayut Public Health Center in 2022 shows only 991 residents had access to proper sanitation. Moreover, of the 748 houses surveyed, only 284 were classified as healthy housing. In 2023, skin diseases ranked among the top ten most common illnesses at the Pegayut Public Health Center, with 115 cases reported. This study aimed to examine the association between environmental sanitation, personal hygiene, and skin complaints among residents of Ibul Besar II Village. Using a cross-sectional design with 142 respondents meeting the inclusion criteria, data were analyzed through univariate, bivariate (chi-square test), and multivariate (multiple logistic regression) methods. The bivariate results showed significant associations between skin complaints and factors such as bathing habits (p = 0.001; OR = 3.402; 95% CI: 1.670–6.931), hand and nail hygiene (p = 0.012; OR = 2.532; 95% CI: 1.276–5.027), clothing hygiene (p = 0.021; OR = 3.000; 95% CI: 1.240–7.255), bedding and bed linen hygiene (p = 0.011; OR = 2.548; 95% CI: 1.286–5.047), faeces disposal facilities (p = 0.011; OR = 2.919; 95% CI: 1.331–6.402), and wastewater disposal systems (p = 0.001; OR = 4.067; 95% CI: 1.804–9.167). Multivariate analysis showed that inadequate wastewater disposal systems had the strongest association with skin health complaints (p = 0.003; OR = 3.959; 95% CI: 1.605–9.758). To prevent skin health issues, priorities should include improving wastewater disposal facilities and promoting better hygiene of bedding and linen. Additionally, community members are encouraged to improve personal hygiene and maintain environmental sanitation to reduce the risk of skin disorders.